Does the elephant dance : contemporary Indian foreign - "Malone,David. M." (New York, 2011)
Does the Elephant Dance? elegantly surveys key features of contemporary Indian foreign policy. David Malone identifies relevant aspects of Indian history, examines the role of domestic politics and internal and external security challenges, and of domestic and international economic factors. He analyses the specifi cs of India's policy within its South Asian neighbourhood, and with respect to China, the USA, West Asia, East Asia, Europe, and Russia as well as multilateral diplomacy. The book also touches on Indian ties to Africa and Latin America, and the Caribbean. India's 'soft power', the role of migration in its policy, and other cross-cutting issues are analysed, as is the role and approach of several categories of foreign policy actors in India. Substantive conclusions touch on policies India may want or need to adjust in its quest for international stature.
Keywords: India